Preparation and in vitro screening of symmetrical bis-isoquinolinium cholinesterase inhibitors bearing various connecting linkage--implications for early Myasthenia gravis treatment - Musilek, Kamil; Komloova, Marketa; Holas, Ondrej; Hrabinova, Martina; Pohanka, Miroslav; Dohnal, Vlastimil; Nachon, Florian; Dolezal, Martin; Kuca, Kamil (European journal of medicinal chemistry, 2011)
Inhibitors of acetylcholinesterase are compounds widely used in the treatment of various diseases, such as Alzheimer's disease, glaucoma and Myasthenia gravis (MG). Compounds used in the therapy of MG posses a positive charge in the molecule to ensure peripheral effect of action and minimal blood-brain barrier penetration. The most prescribed carbamate inhibitors are however known for many severe side effects related to the carbamylation of AChE. This paper describes preparation and in vitro evaluation of 20 newly prepared bis-isoquinolinium inhibitors of potential concern for MG. The newly prepared compounds were evaluated in vitro on human recombinant AChE and human plasmatic butyrylcholinesterase (BChE). Their inhibitory ability was expressed as IC50 and compared to chosen standards ambenonium dichloride, edrophonium chloride, BW284c51 and ethopropazine hydrochloride. Three novel compounds presented promising inhibition (in nM range) of both enzymes in vitro better or similar to edrophonium and BW284c51, but worse to ambenonium. The novel inhibitors did not present higher selectivity toward AChE or BChE. The kinetic assay confirmed non-competitive inhibition of hAChE by two selected promising novel compounds. Two newly prepared compounds were also chosen for docking studies that confirmed apparent π-π or π-cationic interactions aside the cholinesterases catalytic sites. The SAR findings were discussed.
Keywords: Cholinesterase Inhibitors; Recombinant Proteins; Structure-Activity Relationship; myasthenia gravis; molekulární struktura; Molecular Structure; vztah mezi dávkou a účinkem léčiva; acetylcholinesterasa; molekulární modely; vztahy mezi strukturou a aktivitou; rekombinantní proteiny; Models, Molecular; stereoizomerie; Myasthenia Gravis; lidé; isochinoliny; Humans; Butyrylcholinesterase; erytrocyty; Erythrocytes; Isoquinolines; butyrylcholinesterasa; Acetylcholinesterase; cholinesterasové inhibitory; Dose-Response Relationship, Drug; Stereoisomerism